ANALISIS FRAMING NARASI RESPONS MASYARAKAT TERKAIT PROGRAM MAKAN BERGIZI GRATIS (MBG) PADA AKUN MEDIA SOSIAL BADAN GIZI NASIONAL - Ambar Kasturi (Sintesa, 2026)
The Free Nutritious Meals (MBG) Program is one of the government's strategic initiatives aimed at improving public nutrition, particularly among school-age children. The implementation of this program has generated diverse public responses that are reflected in comments posted on the official social media accounts of the National Nutrition Agency. This study aims to analyze the framing of public response narratives regarding the MBG program on the agency's social media platforms. The research employs Robert N. Entman's framing theory, which consists of four analytical elements: define problems, diagnose causes, make moral judgments, and treatment recommendations. A qualitative descriptive approach was used, with data collected through documentation of public comments related to the MBG program. The findings reveal three dominant frames in public responses: a supportive frame that views the program as a positive effort to improve children's nutrition, a critical frame that questions transparency and   implementation effectiveness, and an evaluative frame that emphasizes the importance of supervision and equitable distribution of program benefits. These findings indicate that social media functions not only as a government communication channel but also as a discursive space where the public constructs perceptions and opinions regarding government policies. Keywords: Framing Analysis, Free Nutritious Meals Program, National Nutrition Agency, Social Media, Public Opinion.